KEPEMIMPINAN KETUA ORGANISASI INTRA SEKOLAH SEBAGAI PENGGERAK BUDAYA KOLABORATIF PADA SEKOLAH MENENGAH ATAS NEGERI 3 KOTA JAMBI - Asriani, Winanda; Jamrizal; Hakim, Lukman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the leadership of the Student Council (OSIS) President as the driving force behind the collaborative culture among students at SMA Negeri 3 Kota Jambi for the 2024/2025 period. The research focuses on: (1) the transformational leadership characteristics demonstrated by the OSIS President; (2) charismatic leadership attributes that motivate members; and (3) the synergy between the supervisor, president, and OSIS members in building a collaborative organizational culture. A qualitative case study approach was employed, using in-depth interviews, participatory observations, and documentation analysis. The findings reveal that the OSIS President, Muhammad Faturrahman, consistently and effectively implements the four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Additionally, the president demonstrates charismatic leadership traits, including strong self-confidence, persuasive communication, personal magnetism, and empathetic behavior, which strengthen emotional ties among members. The close synergy between the OSIS supervisors, president, and members fosters a strong collaborative culture characterized by open communication, participatory meetings, clear division of tasks, and a high sense of ownership toward organizational programs. The study concludes that the OSIS President’s leadership plays a central and significant role in shaping a collaborative culture and serves as a relevant model of student leadership aligned with 21st-century educational demands.